Correction: Cyclopeptidic photosensitizer prodrugs as proteolytically triggered drug delivery systems of pheophorbide A: part I – self-quenched prodrugs. Issue 11 (23rd October 2019) - Bouilloux, Jordan; Yushchenko, Oleksandr; Dereka, Bogdan; Boso, Gianluca; Zbinden, Hugo; Vauthey, Eric; Babič, Andréj; Lange, Norbert
Abstract : Correction for 'Cyclopeptidic photosensitizer prodrugs as proteolytically triggered drug delivery systems of pheophorbide A: part I – self-quenched prodrugs' by Jordan Bouilloux et al., Photochem. Photobiol. Sci., 2018, 17, 1728–1738.